2019
DOI: 10.2478/hukin-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

International Standards for the 3‐Minute Burpee Test: High‐ Intensity Motor Performance

Abstract: The aim of this study was to develop international standards for evaluating strength endurance with the use of the 3‐Minute Burpee Test. The results of 3862 women (Poland – 2502, Great Britain – 500, Hungary – 412, Serbia – 448) and 5971 men (Poland – 4517, Great Britain – 500, Hungary – 451, Serbia – 503) aged 18‐25 (mean age of 20.36 ± 0.94 and 20.05 ± 1.25 y, respectively) were collated between 2004 and 2018. The students’ strength endurance was evaluated in the 3‐Minute Burpee Test. The results were expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Coast et al (2004), Courtright,McCormnick, Postlethwaite, Reeves, &Mount (2013)and Ployhart, et al (2006) also demonstrated that males scored substantially better on muscular strength and cardiovascular endurance tests. Similar results were reported in an international study aiming to develop classification standards for endurance-strength abilities based on the 3-MBT (Podstawski et al, 2019). Sex differences are less pronouncedwith regard to muscular strength, and sex differences in muscular strength vary considerably across different body regions.…”
Section: Discussionsupporting
confidence: 85%
“…Coast et al (2004), Courtright,McCormnick, Postlethwaite, Reeves, &Mount (2013)and Ployhart, et al (2006) also demonstrated that males scored substantially better on muscular strength and cardiovascular endurance tests. Similar results were reported in an international study aiming to develop classification standards for endurance-strength abilities based on the 3-MBT (Podstawski et al, 2019). Sex differences are less pronouncedwith regard to muscular strength, and sex differences in muscular strength vary considerably across different body regions.…”
Section: Discussionsupporting
confidence: 85%
“…Strength training and development is considered an essential component for the increase of the population's physical condition 1 and essential for delivering support and maintenance of body posture. 2 It is a fact that the daily movements that people exercise need strength, and that some of these physical efforts are sustained over an extended period 3 ; for these last efforts, strength-resistance (S-R) plays a fundamental role.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no test to evaluate S-R with four consecutive and continuous self-loading exercises at low cost and with qualitative scales indicating different levels of S-R for both men and women. 1 Consequently, this study's primary purpose was to determine the validity and reliability of the Muscular Fitness Test (MFT) to evaluate self-loading body strength-resistance in healthy and physically active young adults from 18 to 25 years old. As a secondary objective, the MFT qualitative scales were created to evaluate the different levels of body S-R in men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Burpee test. All female cadets performed a 3-minute burpee test according to the method of Podstawski (Podstawski et al, 2019). Female cadets were instructed on how to perform the burpee test correctly.…”
Section: The Research Designmentioning
confidence: 99%
“…Despite the unequivocal effectiveness of cardiorespiratory endurance and resistance training, the main factors that discourage individuals from pursuing these types of exercise are the considerable length of training sessions. High-intensity circuit training that relies on body mass for resistance appears to be an effective solution for cardiorespiratory and resistance training (Podstawski et al, 2019). There is scientific evidence of a positive impact of high-intensive jumping workouts on cardiorespiratory fitness and strength endurance of females (Osipov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%